2017
DOI: 10.1021/acs.energyfuels.7b01394
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Interfacial Tension Behavior of Salt Water Containing Dissolved Amphiphilic Compounds of Crude Oil: The Role of Single-Salt Ionic Composition

Abstract: A detailed investigation into the effect of dissolved amphiphilic compounds of crude oil in salt water on its surface tension/interfacial tension (ST/IFT) behavior has been conducted in this paper. To simulate water–oil contact during water injection into oil reservoirs, 16 single-salt aqueous solutions of NaCl, CaCl2, and Na2SO4 having ionic strengths of up to 2.0 M were mixed with a natural acidic–basic crude oil. The mixing was performed by a rocking mechanism in a visual pressure–volume–temperature cell at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 67 publications
(123 reference statements)
5
27
0
Order By: Relevance
“…[ 70 ] Regarding surface activity, several studies show that although small amounts of organic compounds are present in water, these soluble amphiphilic components have a considerable effect on surface/interface property. [ 43,44,54 ] Comparing the results of this work with previous research, it can be concluded that some organic compounds of crude oil are soluble in water and their amount varies according to the type of oil and polar compounds.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…[ 70 ] Regarding surface activity, several studies show that although small amounts of organic compounds are present in water, these soluble amphiphilic components have a considerable effect on surface/interface property. [ 43,44,54 ] Comparing the results of this work with previous research, it can be concluded that some organic compounds of crude oil are soluble in water and their amount varies according to the type of oil and polar compounds.…”
Section: Resultssupporting
confidence: 52%
“…These functionalities alongside organic tail could act as surface‐active components and affect the IFT/ST and wettability. [ 43,44,54 ] The analysis of well‐produced water shows that the most soluble components of crude oil are carboxylic acids with a low molecular weight. [ 72 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude oil contains asphaltenes, resins, and waxes which are considered as the surface-active agent of crude oil and act like a natural surfactant. Previous research found that the natural surfactants in the crude oil (i.e., asphaltenes, resins) have a significant effect on the variation of IFT value of crude oil–brine system [ 40 , 42 , 44 ]. The distribution of asphaltene and resin in the oil phase alters with the enhancement of salinity since the diffusion of asphaltene and resin from the aqueous brine solution to the interface occurs due to the ions of brine.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the dissolution of the crude oil compound by NaCl and subsequent sorption of the amphiphilic compound at the interface of O/W. This liquified crude oil in the NaCl acted as a natural ionic and non-ionic hydrocarbon surfactant [44]. It might also be because of the synergetic influence of the NaCl and CNP on the IFT.…”
Section: Resultsmentioning
confidence: 99%